2013
DOI: 10.1039/c2ta00312k
|View full text |Cite
|
Sign up to set email alerts
|

One-step approach to novel Bi4V2O11hierarchical hollow microspheres with high visible-light-driven photocatalytic activities

Abstract: New visible-light-sensitive hierarchical Bi 4 V 2 O 11 hollow microspheres have been successfully synthesized by a facile template-free solvothermal route. The hierarchical Bi 4 V 2 O 11 superstructure was constructed of single-crystalline nanoplates with a porous surface. A possible growth pattern and formation mechanism of hierarchical Bi 4 V 2 O 11 hollow microspheres was proposed. The Brunauer-Emmett-Teller (BET) surface area of the hollow sample was 84.613 m 2 g À1 , which was much higher than other prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 33 publications
0
29
1
Order By: Relevance
“…Thakral et al [31] firstly investigated the visible-light photocatalytic performance of Bi 4 V 2 O 11 prepared by conventional solid state method. More recently, Chen et al [32] reported Bi 4 V 2 O 11 hollow microspheres with hierarchical superstructures. It has been reported that the optical behavior of Bi 4 V 2 O 11 is highly sensitive to the synthetic conditions [31,33].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Thakral et al [31] firstly investigated the visible-light photocatalytic performance of Bi 4 V 2 O 11 prepared by conventional solid state method. More recently, Chen et al [32] reported Bi 4 V 2 O 11 hollow microspheres with hierarchical superstructures. It has been reported that the optical behavior of Bi 4 V 2 O 11 is highly sensitive to the synthetic conditions [31,33].…”
Section: Introductionmentioning
confidence: 97%
“…It has been reported that the optical behavior of Bi 4 V 2 O 11 is highly sensitive to the synthetic conditions [31,33]. The synthesis method, the morphology and the size of crystals play a crucial role in determining the photocatalytic performance [32].…”
Section: Introductionmentioning
confidence: 99%
“…Many nontypical stoichiometric semiconductor photocatalysts, such as Bi 3 [18], Bi 2 VO 5.5 [19] and W 18 O 49 [20,21], could be qualified as ideal candidates for the construction of heterojunction with nansozied interfacial contact. These nontypical stoichiometric photocatalysts exhibit excellent photocatalytic activity owing to their unique band structure, more strong mobility of charge carriers and effective capacity in separation of photoinduced electron-hole pairs, compared with their corresponding typical stoichiometric semiconductor photocatalysts (BiOX (X = Cl, Br, I), BiVO 4 and WO 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Morphology control is an efficient method to facilitate carrier transportation and light harvesting, accelerate charge movement within the material structure and assist the collection and separation of electron-hole pairs at the interface of the materials [199][200][201][202]. Controllable synthesis of BiVO 4 with controlled morphologies has been notable developed (such as nanorods, nanowires, nanotubes (NTs), nanobelts, nanoellipsoids, hollow spheres, and even some hierarchical architectures) and corresponding morphology-dependent photocatalytic properties have also been extensively studied [203][204][205][206][207][208][209][210][211]. For example, Tada et al first fabricated BiVO 4 nanorods (NRs) using polyethylene glycol (PEG) as a shape−directing agent [203].…”
Section: Bivomentioning
confidence: 99%